A Comprehensive Analysis of the Effect of Employee Rewards on Employee Performance - Mdhlalose, Dickson Scoth (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2023)
Research Aims: The aim of this study is to explore the effects of employee rewards on employee performance. Design/Methodology/Approach: The information utilized in this investigation was already publicly available. Online search engines and associated periodicals were used to compile the secondary data. To back up the research, appropriate textbooks were examined. Research Findings: Both financial rewards and non-financial rewards influence the performance of employees in an organization. However, extrinsic rewards have a short-term effect on employees’ behaviour while intrinsic rewards have a long-term effect. Theoretical Contribution/Originality: The study contributes to theory by advancing the comprehension of the influence of total rewards (financial and non-financial rewards) on the performance of employees. Managerial Implication: The findings of this research will help employees and employers in understanding the critical effects of employee rewards on employee performance. Research Limitation & Implications: This study relied only on secondary sources, and the investigator lacked no means of verifying its accuracy.